Cobalt-based modified industrial solid waste vinegar residue derived carbon composite material as well as preparation method and application thereof
By preparing cobalt-based modified industrial solid waste vinegar slag-derived carbon composite materials, the problems of low conductivity of ZIF-67-derived Co3O4 materials and complex synthesis of nitrogen-doped graphene are solved, and hydrogen peroxide is achieved The rapid identification and detection improves the performance and environmental friendliness of electrochemical sensors.
Patent Information
- Application Number
- CN202411335801.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-24
AI Technical Summary
Among the existing electrochemical sensors, ZIF-67-derived Co3O4 materials have problems with catalyst agglomeration and low conductivity, and the complex, dangerous and high cost of nitrogen-doped graphene has limited its application, and it has failed to effectively utilize industrial solid waste vinegar. Slag acts as a precursor for biomass-derived carbon materials.
By washing, carbonizing, and hot alkali activation of industrial solid waste vinegar residue, reacting with cobalt nitrate and 2-methylimidazole, a cobalt-based modified industrial solid waste vinegar residue derived carbon composite (Co3O4/VRC) is formed, and vinegar residue is used as vinegar residue. The base biomass-derived carbon is a substrate in situ growth Co3O4, which improves conductivity and catalytic activity, and is applied to the working electrode of electrochemical sensors.
It realizes rapid identification and detection of biological molecules such as hydrogen peroxide, improves conductivity and catalytic activity, reduces costs, is simple in process and is environmentally friendly, avoids soil pollution by acid leachate, and has wide application prospects.
Smart Images

Figure CN119176587A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensors, and in particular relates to a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material and a preparation method and application thereof. Background Art
[0002] Electrochemical biosensing analysis technology is widely used in real-time monitoring of biomolecules due to its simple operation, high sensitivity and rapid response. Electrochemical biosensors are divided into natural enzyme type and enzyme-free type, that is, nanomaterial enzyme-like type. Enzyme-based sensors have good selectivity and sensitivity to target small molecules, but their disadvantages are high cost, complex operation and harsh detection conditions. Nanomaterial enzyme-like sensors mainly work by modifying nanomaterials with electrocatalytic activity for targeted biomolecules. They are popular because of their low cost, friendly operation, excellent selectivity and sensitivity. Based on this, the development of high-performance nanomaterials with enzyme-like catalytic activity has become an important task in the exploration and development of electrochemical biosensing analysis technology.
[0003] Low-cost and abundant transition metals have become the star materials for the preparation of enzyme-free electrochemical sensors, especially cobalt tetroxide (CoO4) derived from metal-organic framework (MOF) ZIF-67. 3 O 4 ). ZIF-67 derived Co 3 O 4 Although it has high porosity, controllable chemical properties and structural morphology, and catalytic activity, it still cannot avoid defects such as catalyst agglomeration and low conductivity. More and more studies have found that the in-situ growth strategy based on nitrogen-doped graphene can greatly improve the performance of ZIF-67-derived Co 3 O 4 The conductive properties of nitrogen-doped graphene can be improved to solve the problem of masking of catalytic active sites. However, the complexity, danger and high cost of nitrogen-doped graphene synthesis have greatly limited the application of this type of composite material.
[0004] Biomass-derived carbon materials are a new type of carbon material derived from carbon source organisms in nature. They have the advantages of high specific surface area, stable chemical properties, adjustable morphology and structure, and rich surface oxygen-containing functional groups. They also have simple preparation processes, are environmentally friendly, low cost, and high abundance. The main component of vinegar residue is lignin left over from fermentation of bran and rice husks. It is a kind of acidic and corrosive solid waste with high water content produced by the vinegar industry, with an annual output of about 3 million tons. Directly discarding vinegar residue will cause environmental pollution and waste abundant lignin resources. At present, most of the research focuses on using it as a raw material for anaerobic fermentation, and has not used it as a precursor of biomass-derived carbon. Therefore, it is worth exploring and studying the use of vinegar residue to prepare functional electrochemical biomass-derived carbon-based composite materials. Summary of the invention
[0005] The present application provides a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material and its preparation method and application, which converts acidic solid waste vinegar residue into a functionalized carbon-based material, and applies it to an electrochemical sensor to achieve rapid identification and detection of biological molecules such as hydrogen peroxide.
[0006] In a first aspect, the present application provides a method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material, comprising the following steps: S1. Washing, drying, crushing and sieving industrial solid waste vinegar residue to obtain clean vinegar residue powder; the solid waste vinegar residue comes from various vinegar production enterprises in China; S2. Carbonizing the vinegar residue powder under an inert atmosphere to obtain carbonized vinegar residue; S3, mixing the carbonized vinegar residue in a 10% KOH hot solution for activation, aging, centrifuging, washing, drying, grinding, and sieving to obtain an industrial solid waste vinegar residue derived carbon material (VRC); S4, weighing a certain amount of the industrial solid waste vinegar residue derived carbon material and dispersing it in cobalt nitrate, hexadecyltrimethylammonium bromide and methanol solution, stirring at a uniform speed, and recording it as solution A; S5. Weigh a certain amount of 2-methylimidazole, disperse it in methanol, stir it thoroughly and prepare solution B; S6, slowly pouring the solution B into the solution A, stirring at a uniform speed, centrifuging, washing, drying, and grinding to obtain a ZIF-67 / VRC complex; S7, pyrolyzing the ZIF-67 / VRC composite in an inert atmosphere, cooling naturally, and then calcining in an air atmosphere to obtain a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material (Co 3 O 4 / VRC).
[0007] Optionally, the mass ratio of the industrial solid waste vinegar residue-derived carbon material, cobalt nitrate, hexadecyltrimethylammonium bromide, and 2-methylimidazole in solution A and solution B is 0.125:0.872:0.06:0.986.
[0008] Optionally, in step S1, the drying temperature is 60° C., and the drying time is 12 h to 24 h; the washing solvent is deionized water and anhydrous ethanol; and the sieving mesh size is 100 mesh.
[0009] Optionally, in step S2, the carbonization heating rate is 2°C / min; the carbonization temperature is 600°C-900°C; and the carbonization time is 2 h.
[0010] Optionally, in step S3, the mass ratio of the carbonized vinegar residue to potassium hydroxide is 10:1, the temperature of the 10% KOH hot solution is 80°C; the activation time is 1 h, the aging time is 24 h; the centrifugal speed is 11000 rpm, the time is 10 min; the sieving mesh size is 100 mesh.
[0011] Optionally, in step S6, the uniform stirring reaction time is 12-36 h, the centrifugal speed is 11000 rpm, and the time is 10 min; the washing dispersant used is anhydrous ethanol; the centrifugal speed is 11000 rpm, and the time is 10 min; and the drying time is 12 h-24 h.
[0012] Optionally, in step S7, the pyrolysis temperature in the inert atmosphere is 700°C, and the holding time is 2 h; the calcination temperature in the air atmosphere is 150°C-300°C, and the holding time is 12 h.
[0013] Optionally, in step S2 and step S7, the inert atmosphere is any one of high-purity argon and high-purity nitrogen.
[0014] In a second aspect, the present application provides a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material, which is prepared using vinegar residue-based biomass-derived carbon as a substrate.
[0015] In the third aspect, the present application provides an application of a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material. The cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material prepared in the present application is used in the preparation of working electrodes for electrochemical biosensors.
[0016] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art: (1) The present invention uses industrial solid waste vinegar residue as a precursor, and obtains a biomass carbon material with rich wrinkles and porous surface and self-doped nitrogen through high-temperature calcination and hot alkali activation. This biomass-derived carbon material has a wide source, low cost, simple and safe process, strong repeatability, and can be produced on a large scale. The acidic solid waste vinegar residue is converted into a functional carbon-based material, avoiding the secondary pollution of the soil by the acidic leachate caused by direct landfill, which is environmentally friendly and realizes carbon cycle.
[0017] (2) The present invention uses vinegar residue-derived carbon material as a substrate to in-situ grow Co 3 O 4 The prepared cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material was used as the working electrode modification material of the electrochemical sensor. 3 O 4The particles grow evenly on the VRC surface with rich wrinkled pores, and the two interact through electrostatic attraction and cobalt-carbon bonding. Compared with the electrocatalytic performance of a single component, it effectively improves the conductivity and increases the specific surface area. The self-nitrogen doping and cobalt-carbon bonding effectively improve the electron transfer efficiency, thereby enhancing the electrode's adsorption of biological molecules such as hydrogen peroxide and providing more catalytic active sites, achieving rapid recognition and detection of biological molecules such as hydrogen peroxide.
[0018] (3) The present invention uses cobalt-based modified industrial solid waste vinegar residue-derived carbon composite materials as nanomaterial mimic enzymes to build a high-performance biomolecule electrochemical sensing analysis and detection platform, achieving high-sensitivity, low-detection-limit specific analysis of biomolecules such as hydrogen peroxide, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Characterization diagram of the surface morphology of different materials in Test Example 1 of the present invention; wherein a is the SEM image of VRC synthesized in Comparative Example 1; b is the SEM image of Co synthesized in Example 1 3 O 4 / SEM image of VRC.
[0020] Figure 2 Co in Test Example 1 of the present invention 3 O 4 / distribution diagram of each element in VRC; wherein a is Co in Example 1 3 O 4 / VRC; b is the SEM image of Co in Example 1 3 O 4 / element distribution diagram of C in VRC; c is Co in Example 1 3 O 4 / N element distribution diagram of VRC; d is Co in Example 1 3 O 4 / is the element distribution diagram of O of VRC; e is the element distribution diagram of Co.
[0021] Figure 3 Characterization diagram of element binding states of different materials in Test Example 2 of the present invention; wherein a is Co in Example 1 3 O 4 / VRC, VRC synthesized in Comparative Example 1, Co synthesized in Comparative Example 2 3 O 4 The XPS full spectrum of Co in Example 1 3 O 4 / VRC, C 1s high resolution spectrum of VRC synthesized in Comparative Example 1; c is Co 3 O 4 / VRC, O 1s high-resolution spectrum of VRC synthesized in Comparative Example 1; d is Co3 O 4 / VRC, N 1s high-resolution spectrum of VRC synthesized in Comparative Example 1; e is Co in Example 1 3 O 4 / VRC, Co synthesized in Comparative Example 2 3 O 4 High-resolution spectrum of Co 2p.
[0022] Figure 4 Co synthesized from Example 1 in Test Example 3 of the present invention 3 O 4 / VRC, Co synthesized in Comparative Example 2 3 O 4 CV curves of the modified glassy carbon electrode tested in a 4 mM hydrogen peroxide solution, where a represents the Co prepared in Comparative Example 2 3 O 4 CV curves of the modified electrode in electrolyte without hydrogen peroxide; b represents the Co prepared in comparative example 2 3 O 4 CV curves of the modified electrode in a 4 mM hydrogen peroxide solution; c represents the Co prepared in Example 1 3 O 4 CV curves of the Co / VRC modified electrode in electrolyte without hydrogen peroxide; d represents the CV curves of the Co / VRC modified electrode prepared in Example 1. 3 O 4 CV curves of / VRC modified electrode in 4 mM hydrogen peroxide solution.
[0023] Figure 5 Co synthesized from Example 1 in Test Example 3 of the present invention 3 O 4 / VRC linear response range test for hydrogen peroxide; a is Co prepared in Example 1 3 O 4 CV response of the Co / VRC modified electrode to 1-600 μM hydrogen peroxide molecules; b is the CV response of the Co / VRC modified electrode to 1-600 μM hydrogen peroxide molecules; 3 O 4 Linear fitting plot of CV response current size of / VRC modified electrode to hydrogen peroxide and hydrogen peroxide concentration.
[0024] Figure 6 Co prepared in Example 1 of Test Example 3 of the present invention 3 O 4 Selectivity test of / VRC modified electrode for hydrogen peroxide. DETAILED DESCRIPTION
[0025] In one embodiment of the present application, a method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material comprises the following steps: S1. Washing, drying, crushing and sieving industrial solid waste vinegar residue to obtain clean vinegar residue powder; the solid waste vinegar residue comes from various vinegar production enterprises in China; S2. Carbonizing the vinegar residue powder under an inert atmosphere to obtain carbonized vinegar residue; S3, mixing the carbonized vinegar residue in a 10% KOH hot solution for activation, aging, centrifuging, washing, drying, grinding, and sieving to obtain an industrial solid waste vinegar residue derived carbon material (VRC); S4, weighing a certain amount of the industrial solid waste vinegar residue derived carbon material and dispersing it in cobalt nitrate, hexadecyltrimethylammonium bromide and methanol solution, stirring at a uniform speed, and recording it as solution A; S5. Weigh a certain amount of 2-methylimidazole, disperse it in methanol, stir it thoroughly and prepare solution B; S6, slowly pouring the solution B into the solution A, stirring at a uniform speed, centrifuging, washing, drying, and grinding to obtain a ZIF-67 / VRC complex; S7, pyrolyzing the ZIF-67 / VRC composite in an inert atmosphere, cooling naturally, and then calcining in an air atmosphere to obtain a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material (Co 3 O 4 / VRC).
[0026] In this application, the present invention adopts an in situ growth strategy to prepare ZIF-67 derived Co using vinegar residue-based biomass-derived carbon as a substrate. 3 O 4 The composite material has excellent electrical conductivity, realizes self-nitrogen doping and metal-carbon fusion, provides more reactive sites and higher catalytic activity for the detection of target biological target molecules, and realizes rapid identification and detection of biological molecules such as hydrogen peroxide, which is of great significance for realizing early diagnosis of diseases. In the preparation process, the cobalt salt used in the present invention is an inorganic salt, and cobalt tetraoxide is prepared by ZIF-67 derivatization, which has more catalytic active sites. The present invention is an open system reaction at room temperature, which is safe, stable and easy to operate. The present invention first carbonizes the biomass, removes impurities of other fats and oils outside the carbon skeleton, and then performs hot alkali activation, so that the activation efficiency is higher and irrelevant side reactions are avoided.
[0027] As an optional embodiment, the raw materials of the carbon composite material are further limited, and the mass ratio of the industrial solid waste vinegar residue-derived carbon material, cobalt nitrate, hexadecyltrimethylammonium bromide (CTAB), and 2-methylimidazole in solution A and solution B is 0.125:0.872:0.06:0.986.
[0028] As an optional embodiment, the pretreatment process conditions of the industrial solid waste vinegar residue are further limited. In step S1, the drying temperature is 60°C, and the drying time is 12 h to 24 h; the washing solvent is deionized water and anhydrous ethanol; and the sieving mesh size is 100 mesh.
[0029] As an optional embodiment, the carbonization process conditions of the industrial solid waste vinegar residue are further limited. In step S2, the carbonization heating rate is 2°C / min; the carbonization temperature is 600-900°C; and the carbonization time is 2 h.
[0030] As an optional embodiment, the mass ratio of carbonized vinegar residue to potassium hydroxide is further limited. In step S3, the mass ratio of carbonized vinegar residue to potassium hydroxide is 10:1.
[0031] As an optional embodiment, the process conditions of hot alkali activation are further limited. In step S3, the temperature of the 10% KOH hot solution is 80°C; the activation time is 1 h, and the aging time is 24 h; the centrifugal speed is 11000 rpm, and the time is 10 min; and the sieving mesh size is 100 mesh.
[0032] As an optional embodiment, for Co 3 O 4 In situ growth of Co 3 O 4 The reaction conditions are further limited. In step S6, the uniform stirring reaction time is 12-36 h, the centrifugal speed is 11000 rpm, and the time is 10 min; the washing dispersant used is anhydrous ethanol; the centrifugal speed is 11000 rpm, and the time is 10 min; the drying time is 12h-24h.
[0033] As an optional embodiment, the pyrolysis conditions of the composite material are further limited. In step S7, the pyrolysis temperature in the inert atmosphere is 700°C, and the holding time is 2 h; the calcination temperature in the air atmosphere is 150°C-300°C, and the holding time is 12 h.
[0034] As an optional embodiment, the inert atmosphere is further limited. In step S2 and step S7, the inert atmosphere is any one of high-purity argon and high-purity nitrogen.
[0035] In addition, the present application provides an application of a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material, and the cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material prepared in the present application is applied to the preparation of a working electrode of an electrochemical biosensor.
[0036] Example 1 A method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material comprises the following steps: S1. The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; S2. In a high-purity argon atmosphere, the clean and dry vinegar residue powder is kept at 800° C. for 2 h at a heating rate of 2° C. / min in a tube furnace, and ground to obtain carbonized vinegar residue; S3, dispersing 500 mg of the carbonized vinegar residue in 50 ml of a 10% hot KOH solution, placing it on a constant temperature magnetic stirrer and stirring it at a uniform speed, keeping it at 80°C for 1 hour, stopping heating, cooling it naturally to room temperature and aging it for 24 hours; then centrifuging it at 10000 rpm for 10 minutes, removing the supernatant, and soaking the obtained precipitate in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, centrifuging it with deionized water and ethanol in turn, and washing it to neutrality; finally, placing the precipitate in an 80°C forced air drying oven for 24 hours, grinding it, and passing it through a 100-mesh sieve to obtain an industrial solid waste vinegar residue-derived carbon material (VRC); S4. Measure 30 ml of methanol in a beaker, weigh 872 mg of cobalt nitrate and 60 mg of CTAB, place them in the beaker, and stir them thoroughly to obtain a cobalt nitrate / CTAB / methanol solution; then add 125 mg of VRC, stir at a constant speed for 30 min, and obtain a uniformly dispersed solution A; S5. Measure 10 ml of methanol into a beaker, weigh 986 mg of 2-methylimidazole, disperse it in the methanol, stir thoroughly and prepare solution B; S6. Slowly pour the solution B into the solution A, stir at a constant speed for 36 h, then centrifuge at 11000 rpm for 10 min, carefully remove the supernatant, centrifuge and wash three times with anhydrous ethanol; vacuum dry the obtained black purple precipitate at 60° C. for 12 h, grind to obtain a ZIF-67 / VRC complex; S7, pyrolyzing the ZIF-67 / VRC composite at 700°C for 2 h in high-purity argon at a heating rate of 2°C / min, and grinding it into powder after natural cooling; then keeping the ground powder at 150°C for 2 h in an air atmosphere at a heating rate of 2°C / min, cooling it naturally, and grinding it into powder to obtain a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material (Co 3 O 4 / VRC).
[0037] Example 2 A method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material comprises the following steps: S1. The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; S2. In a high-purity argon atmosphere, the clean and dry vinegar residue powder is kept at 700° C. for 2 h at a heating rate of 2° C. / min in a tube furnace, and ground to obtain carbonized vinegar residue; S3, dispersing 500 mg of the carbonized vinegar residue in 50 ml of a 10% hot KOH solution, placing it on a constant temperature magnetic stirrer and stirring it at a uniform speed, keeping it at 80°C for 1 hour, stopping heating, cooling it naturally to room temperature and aging it for 24 hours; then centrifuging it at 10000 rpm for 10 minutes, removing the supernatant, and soaking the obtained precipitate in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, centrifuging it with deionized water and ethanol in turn, and washing it to neutrality; finally, placing the precipitate in an 80°C forced air drying oven for 24 hours, grinding it, and passing it through a 100-mesh sieve to obtain an industrial solid waste vinegar residue-derived carbon material (VRC); S4. Measure 30 ml of methanol in a beaker, weigh 872 mg of cobalt nitrate and 60 mg of CTAB, place them in the beaker, and stir them thoroughly to obtain a cobalt nitrate / CTAB / methanol solution; then add 125 mg of VRC, stir at a constant speed for 30 min, and obtain a uniformly dispersed solution A; S5. Measure 10 ml of methanol into a beaker, weigh 986 mg of 2-methylimidazole, disperse it in the methanol, stir thoroughly and prepare solution B; S6. Slowly pour the solution B into the solution A, stir at a constant speed for 36 hours, then centrifuge at 11000 rpm for 10 minutes, carefully remove the supernatant, centrifuge and wash three times with anhydrous ethanol; vacuum dry the obtained black purple precipitate at 60 °C for 12 hours, grind to obtain ZIF-67 / VRC complex; S7, pyrolyzing the ZIF-67 / VRC composite at 700°C for 2 h in high-purity argon at a heating rate of 2°C / min, and grinding it into powder after natural cooling; then keeping the ground powder at 150°C for 2 h in an air atmosphere at a heating rate of 2°C / min, cooling it naturally, and grinding it into powder to obtain a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material (Co 3 O 4 / VRC).
[0038] Example 3 A method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material comprises the following steps: S1. The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; S2. In a high-purity argon atmosphere, the clean and dry vinegar residue powder is carbonized in a tube furnace at 900° C. for 2 h at a heating rate of 2° C. / min to obtain carbonized vinegar residue; S3, dispersing 500 mg of the carbonized vinegar residue in 50 ml of a 10% hot KOH solution, placing it on a constant temperature magnetic stirrer and stirring it at a uniform speed, keeping it at 80°C for 1 hour, stopping heating, cooling it naturally to room temperature and aging it for 24 hours; then centrifuging it at 10000 rpm for 10 minutes, removing the supernatant, and soaking the obtained precipitate in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, centrifuging it with deionized water and ethanol in turn, and washing it to neutrality; finally, placing the precipitate in an 80°C forced air drying oven for 24 hours, grinding it, and passing it through a 100-mesh sieve to obtain an industrial solid waste vinegar residue-derived carbon material (VRC); S4. Measure 30 ml of methanol in a beaker, weigh 872 mg of cobalt nitrate and 60 mg of CTAB, place them in the beaker, and stir them thoroughly to obtain a cobalt nitrate / CTAB / methanol solution; then add 125 mg of VRC, stir at a constant speed for 30 min, and obtain a uniformly dispersed solution A; S5. Measure 10 ml of methanol into a beaker, weigh 986 mg of 2-methylimidazole, disperse it in the methanol, stir thoroughly and prepare solution B; S6. Slowly pour the solution B into the solution A, stir at a constant speed for 36 h, then centrifuge at 11000 rpm for 10 min, carefully remove the supernatant, centrifuge and wash three times with anhydrous ethanol; vacuum dry the obtained black purple precipitate at 60 °C for 12 h, grind to obtain ZIF-67 / VRC complex; S7, pyrolyzing the ZIF-67 / VRC composite at 700°C for 2 h in high-purity argon at a heating rate of 2°C / min, and grinding it into powder after natural cooling; then keeping the ground powder at 150°C for 2 h in an air atmosphere at a heating rate of 2°C / min, cooling it naturally, and grinding it into powder to obtain a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material (Co 3 O 4 / VRC).
[0039] Example 4 A method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material comprises the following steps: S1. The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; S2. In a high-purity argon atmosphere, the clean and dry vinegar residue powder is carbonized in a tube furnace at 600° C. for 2 h at a heating rate of 2° C. / min to obtain carbonized vinegar residue; S3, dispersing 500 mg of the carbonized vinegar residue in 50 ml of a 10% hot KOH solution, placing it on a constant temperature magnetic stirrer and stirring it at a uniform speed, keeping it at 80°C for 1 hour, stopping heating, cooling it naturally to room temperature and aging it for 24 hours; then centrifuging it at 10000 rpm for 10 minutes, removing the supernatant, and soaking the obtained precipitate in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, centrifuging it with deionized water and ethanol in turn, and washing it to neutrality; finally, placing the precipitate in an 80°C forced air drying oven for 24 hours, grinding it, and passing it through a 100-mesh sieve to obtain an industrial solid waste vinegar residue-derived carbon material (VRC); S4. Measure 30 ml of methanol in a beaker, weigh 872 mg of cobalt nitrate and 60 mg of CTAB, place them in the beaker, and stir them thoroughly to obtain a cobalt nitrate / CTAB / methanol solution; then add 125 mg of VRC, stir at a constant speed for 30 min, and obtain a uniformly dispersed solution A; S5. Measure 10 ml of methanol into a beaker, weigh 986 mg of 2-methylimidazole, disperse it in the methanol, stir thoroughly and prepare solution B; S6. Slowly pour the solution B into the solution A, stir at a constant speed for 36 h, then centrifuge at 11000 rpm for 10 min, carefully remove the supernatant, centrifuge and wash three times with anhydrous ethanol; vacuum dry the obtained black purple precipitate at 60 °C for 12 h, grind to obtain ZIF-67 / VRC complex; S7, pyrolyzing the ZIF-67 / VRC composite at 700°C for 2 h in high-purity argon at a heating rate of 2°C / min, and grinding it into powder after natural cooling; then keeping the ground powder at 150°C for 2 h in an air atmosphere at a heating rate of 2°C / min, cooling it naturally, and grinding it into powder to obtain a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material (Co 3 O 4 / VRC).
[0040] Comparative Example 1 A method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material comprises the following steps: S1. The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; S2. In a high-purity argon atmosphere, the clean and dry vinegar residue powder is carbonized in a tube furnace at 800° C. for 2 h at a heating rate of 2° C. / min to obtain carbonized vinegar residue; S3, dispersing 500 mg of the carbonized vinegar residue in 50 ml of a 10% hot KOH solution, placing it on a constant temperature magnetic stirrer and stirring it at a uniform speed, keeping it at 80°C for 1 hour, stopping heating, cooling it naturally to room temperature and aging it for 24 hours; then centrifuging it at 10000 rpm for 10 minutes, removing the supernatant, and soaking the obtained precipitate in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, centrifuging it with deionized water and ethanol in turn, and washing it to neutrality; finally, placing the precipitate in an 80°C forced air drying oven for 24 hours, grinding it, and passing it through a 100-mesh sieve to obtain an industrial solid waste vinegar residue-derived carbon material (VRC); Comparative Example 2 A method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material comprises the following steps: S1. Measure 30 ml of methanol in a beaker, weigh 872 mg of cobalt nitrate and 60 mg of CTAB, place them in the beaker, and stir them thoroughly to obtain a cobalt nitrate / CTAB / methanol solution; then add 125 mg of VRC and stir at a constant speed for 30 min to obtain a uniformly dispersed solution A; S2. Measure 10 ml of methanol into a beaker, weigh 986 mg of 2-methylimidazole, disperse it in the methanol, stir thoroughly and prepare solution B; S3, slowly pouring the solution B into the solution A, stirring at a constant speed for 36 h, then centrifuging at 11000 rpm for 10 min, carefully removing the supernatant, centrifuging and washing with anhydrous ethanol for 3 times; vacuum drying the obtained black purple precipitate at 60 °C for 12 h, grinding, and obtaining ZIF-67; S4, pyrolyzing the ZIF-67 composite at 700 °C for 2 h in high-purity argon at a heating rate of 2 °C / min, naturally cooling, and grinding into powder; then, heating the ground powder at 150 °C for 2 h in an air atmosphere at a heating rate of 2 °C / min, naturally cooling, and grinding into powder to obtain Co 3 O 4 .
[0041] Test Example 1 Based on Example 1 and Comparative Example 1, Co 3 O 4 / VRC, VRC to characterize and analyze the surface morphology of the material, the results are as follows Figure 1-2 As shown. Figure 1 a It can be seen that the rich convex wrinkled porous structure on the VRC surface gives the material good mass transfer ability, ensuring that the biological target molecules to be detected are fully adsorbed and ensure that they are combined with the electrocatalyst Co 3 O 4 Full contact. Figure 1 b can be seen, Co 3 O 4 Relatively uniform distribution on the VRC surface ensures full exposure of catalytic active sites. Figure 2 It can be seen that C, N, O, and Co elements are evenly distributed in Co 3 O 4 On the surface of / VRC composite materials, in-situ growth of Co was achieved using VRC as a substrate. 3 O 4 , indicating that the synthesized Co 3 O 4 VRC completes self-doping with N and combines with externally modified Co elements to realize graphitization of biomass at carbonization temperature. 3 O 4 The carbon material will be evenly doped to produce more active sites, so that the dual functionalization of Co and N can be completed on the carbon skeleton, promoting a rapid response to the target species.
[0042] Test Example 2 Based on Example 1, Comparative Example 1 and Comparative Example 2, Co 3 O 4 / VRC、VRC、Co 3 O 4 XPS characterization and analysis of the surface elements of the material, the results are as follows Figure 3 As shown. Figure 3 a It can be seen that in addition to the characteristic peaks of C, O, and N elements, Co 3 O 4 / VRC also has obvious characteristic peaks of Co element, and the characteristic peaks of N element are significantly enhanced. The high-magnification scanning spectra of C, O, N, and Co elements on the surface of the material are fitted and analyzed ( Figure 3 be), it was observed that compared with VRC, Co 3 O 4 Almost all C 1s peaks and O1s peaks of VRC shift to lower binding energies, indicating that Co 3 O 4 The electrons were obtained from VRC; Co 3 O 4The main peak of the N 1s spectrum of / VRC is significantly enhanced and a Co-N characteristic peak appears, which is mainly due to the decomposition of ZIF-67; Co 3 O 4 In the VRC, Co2p spin-orbit splitting occurs at 779.98 eV and 794.94 eV, corresponding to the Co 2p3 / 2 and Cop1 / 2 regions, respectively, with a spin energy difference of 14.96 eV. 3 O 4 The characteristic peak position of Co 3+ 2p3 / 2 spectrum 778.18ev characteristic peak corresponds to Co-C x , further confirming that Co 3 O 4 There is electron transfer between Co and VRC; the above analysis shows that 3 O 4 / VRC composites were successfully prepared.
[0043] Test Example 3 Based on Example 1 and Comparative Example 2, the electrochemical performance of the hydrogen peroxide sensor constructed by the cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material was analyzed. 3 O 4 / VRC, Comparative Example 2 Synthesis of Co 3 O 4 The hydrogen peroxide molecule was tested by modifying the material (7.5 μL 5 mg / mL) on the glassy carbon electrode (GCE) using a standard three-electrode system. The redox reaction at the electrode interface was tested and analyzed using cyclic voltammetry (CV) and chronoamperometry (IT). The results are shown in Figure 2. Figure 4-6 shown.
[0044] from Figure 4 It can be seen that Figure 4 The Co synthesized in Example 3 is shown 3 O 4 / VRC and Co synthesized in Comparative Example 2 3 O 4 The electrocatalytic performance of 4 mM hydrogen peroxide showed that 3 O 4 In comparison, Co 3 O 4 The CV curve area of the / VRC increased significantly, indicating that the addition of VCR can effectively increase the conductivity of the electrocatalytic material. After adding hydrogen peroxide, Co 3 O 4 The catalytic current of the CV curve of Co / VRC increased significantly at around 0.186 V, indicating that 3 O 4The catalytic activity of VRC is stronger than that of pure Co 3 O 4 .
[0045] from Figure 5 It can be seen that Figure 5 a shows the Co prepared in Example 3 3 O 4 / VRC detection of different concentrations of hydrogen peroxide, the results show that the CV can detect as low as 5 μM hydrogen peroxide, and the detection range of the sensor is 1-600 μM ( Figure 5 b) By calculation, it can be found that the detection limit of the sensor is as low as 0.115 μM.
[0046] from Figure 6 It can be seen that by testing different interferences to analyze the selectivity of the electrode modified by vinegar residue-based biomass carbon material for detecting hydrogen peroxide, the sensor is sensitive to hydrogen peroxide (H 2 O 2 ) had the highest oxidation current response, and to 10 times the concentration of nitrite ions (NO 2 - ) slightly responded to 10 times the concentration of uric acid (UA) and potassium ions (K + ) Nitrite ion (NO 2 - ) and glucose (Glu) had almost no response, which proved that the material had excellent anti-interference ability and could still maintain a rapid response to hydrogen peroxide in the presence of interfering substances.
Claims
1. A method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material, characterized in that: The following steps are involved: S1. Washing, drying, crushing and sieving the industrial solid waste vinegar residue to obtain clean vinegar residue powder; S2. Carbonizing the vinegar residue powder under an inert atmosphere to obtain carbonized vinegar residue; S3, mixing the carbonized vinegar residue in a 10% KOH hot solution for activation, aging, centrifuging, washing, drying, grinding, and sieving to obtain an industrial solid waste vinegar residue-derived carbon material; S4, weighing a certain amount of the industrial solid waste vinegar residue derived carbon material and dispersing it in cobalt nitrate, hexadecyltrimethylammonium bromide and methanol solution, stirring at a uniform speed, and recording it as solution A; S5. Weigh a certain amount of 2-methylimidazole, disperse it in methanol, stir it thoroughly and prepare solution B; S6, slowly pouring the solution B into the solution A, stirring at a uniform speed, centrifuging, washing, drying, and grinding to obtain a ZIF-67 / VRC complex; S7. Pyrolyzing the ZIF-67 / VRC composite in an inert atmosphere, naturally cooling it, and then calcining it in an air atmosphere to obtain a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material.
2. The method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material according to claim 1, characterized in that: The mass ratio of the industrial solid waste vinegar residue-derived carbon material, cobalt nitrate, hexadecyltrimethylammonium bromide, and 2-methylimidazole in the solution A and the solution B is 0.125:0.872:0.06:0.
986.
3. The method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material according to claim 1, characterized in that: In step S1, the drying temperature is 60°C, the drying time is 12 h to 24 h, and the sieving mesh size is 100 mesh.
4. The method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material according to claim 1, characterized in that: In step S2, the carbonization temperature rise rate is 2°C / min; the carbonization temperature is 600-900°C; and the carbonization time is 2 h.
5. The method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material according to claim 1, characterized in that: In step S3, the mass ratio of the carbonized vinegar residue to potassium hydroxide is 10:1, the temperature of the 10% KOH hot solution is 80°C; the activation time is 1 h, the aging time is 24 h; the centrifugal speed is 11000 rpm, the time is 10 min; the sieving mesh size is 100 mesh.
6. The method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material according to claim 1, characterized in that: In step S6, the uniform stirring reaction time is 12-36 h, the centrifugal speed is 11000 rpm, and the time is 10 min; the washing dispersant used is anhydrous ethanol; the centrifugal speed is 11000 rpm, and the time is 10 min; the drying time is 12 h-24 h.
7. The method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material according to claim 1, characterized in that: In step S7, the pyrolysis temperature in the inert atmosphere is 700°C, and the holding time is 2 h; the calcination temperature in the air atmosphere is 150°C-300°C, and the holding time is 12 h.
8. The method for preparing a cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material according to claim 1, characterized in that: In step S2 and step S7, the inert atmosphere is any one of argon and nitrogen.
9. A cobalt-based modified industrial solid waste vinegar residue derived carbon composite material, characterized in that: The cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material is prepared by any one of the preparation methods of claims 1 to 8.
10. An application of a cobalt-based modified industrial solid waste vinegar residue derived carbon composite material, characterized in that: The cobalt-based modified industrial solid waste vinegar residue-derived carbon composite material prepared according to any one of claims 1 to 9 is used in the preparation of working electrodes for electrochemical biosensors.
Citation Information
Cited By
Electrochemical sensor based on cobaltosic oxide-vinegar residue derived N-doped porous carbon and application of electrochemical sensor in dopamine detection
CN119246631A
An electrochemical sensor based on cobalt tetroxide-vinegar residue-derived N-doped porous carbon and its application in dopamine detection
CN119246631B
